PERUBAHAN ISTILAH KEKERABATAN DAN HUBUNGANNYA DENGAN SISTEM KEKERABATAN PADA MASYARAKAT MINANGKABAU - Sri Meiyenti; Syahrizal . (Universitas Andalas, 2014)
This article talks about the changes that occur in the Minangkabau kinship. Aspect of concern is about the kinship term system in relate with term of reference and term of address. Kinship term system have consequence in the rights and obligations. Changes in the kinship term system causes changes to the rights and obligations of kinship in the Minangkabau society